Molecular Characterization of Upper Tract Urothelial Carcinoma in the Era of Next-generation Sequencing: A Systematic Review of the Current Literature - Hassler, Melanie R.; Bray, Freddie; Catto, James W.F.; Grollman, Arthur P.; Hartmann, Arndt; Margulis, Vitaly; Matin, Surena F.; Roupret, Morgan; Sfakianos, John P.; Shariat, Shahrokh F.; Faltas, Bishoy M. (European Urology, 2020)
Context: While upper tract urothelial carcinoma (UTUC) share histological appearance with bladder cancer (BC), the former has differences in etiology and clinical phenotype consistent with characteristic molecular alterations. Objective: To systematically evaluate current genomic sequencing and proteomic data examining molecular alterations in UTUC. Evidence acquisition: A systematic review using PubMed, Scopus, and Web of Science was performed in December 2019 according to the Preferred Reporting Items for Systematic Reviews and Meta-analyses statement. Evidence synthesis: A total of 46 publications were selected for inclusion in this report, including 13 studies assessing genome-wide alterations, 18 studies assessing gene expression or microRNA expression profiles, three studies assessing proteomics, one study assessing genome-wide DNA methylation, and 14 studies evaluating distinct pathway alteration patterns. Differences between sporadic and hereditary UTUC, and between UTUC and BC, as well as molecular profiles associated with exposure to aristolochic acid are highlighted. Molecular pathways relevant to UTUC biology, such as alterations in FGFR3, TP53, or microsatellite instability, are discussed. Our findings are limited by tumor and patient heterogeneity and different platforms used in the studies. Conclusions: Molecular events in UTUC and BC can be shared or distinct. Consequently, molecular subtypes differ according to location. Further work is needed to define the epigenomic and proteomic features of UTUC, and understand the mechanisms by which they shape the clinical behavior of UTUC. Patient summary: We report the current data on the molecular alterations specific to upper tract urothelial carcinoma (UTUC), resulting from novel genomic and proteomic technologies. Although UTUC biology is comparable with that of bladder cancer, the rates and UTUC-enriched alterations support its uniqueness and the need for precision medicine strategies for this rare tumor type. Recent data obtained by high-throughput molecular profiling technologies underscore the distinct molecular alterations found in upper tract urothelial carcinoma (UTUC). UTUC biology shares many features with bladder cancer, but there are important specific distinctions that support the need for UTUC-targeted therapeutic strategies.
CRIS-Team Scopus Importer:2020-06-30
Keywords: Genomics; Molecular alterations; Molecular characterization; Next-generation sequencing; Proteomics; Renal pelvis; RNAseq; Transcriptomics; Ureter; Urothelial carcinoma